Sustainable Stingless Beekeeping for Rural Socioeconomic Transformation An Asset-Based Community Approach - Fajar Budiman; Novi Aldi; Farida Aini; Nar Fizan (Universitas Nurul Jadid, 2026)
Rural poverty in agricultural regions is often exacerbated by limited livelihood diversification and the underutilization of abundant local natural resources. This program addresses the urgent need for sustainable economic alternatives by enhancing community capacity through stingless bee (kelulut) cultivation using the Asset-Based Community Development (ABCD) approach. The methodology followed a structured four-stage process: asset mapping, technical training in beekeeping, continuous mentoring, and the institutionalization of community business groups. Results indicate a significant improvement in technical proficiency among participants, particularly in colony management and hygienic harvesting techniques. The program successfully established independent business groups and achieved measurable income diversification, with honey and its derivatives providing a new, stable value-added revenue stream for households. Beyond economic gains, the initiative resulted in a 45.7% increase in environmental awareness regarding pollination services. Ultimately, this program provides a replicable model for green economic development and sustainable rural transformation through the strategic mobilization of local biodiversity and social capital.